Gall bladder agenesis: a surgeon’s dilemma - Joseph, Jebin; Kumar, Arun (International Surgery Journal, 2019)
Congenital agenesis of gall bladder is a rare anomaly which poses a diagnostic dilemma to the surgical fraternity. Ultrasonography, which is the standard investigation of choice in gall bladder diseases often gives a mistaken diagnosis of cholelithiasis in the background of a shrunken gall bladder with hyperechoic shadows suggestive of gall stones. Intra-operatively this poses a surprise to the operating surgeon who fails to locate gall bladder in its normal anatomic position as well as any of the ectopic sites. The controversy in further course of management whether to abandon the procedure and follow-up with a post-operative imaging such as MRCP or to convert the laparoscopic procedure into an open surgery has been a debate for the surgeons. Most of the literature favours the first approach, thereby reducing the morbidity associated with the surgery. In this case report we present a 42-year-old male who presented with symptoms of gall bladder disease to a peripheral surgical centre and how we approached the intra-operative dilemma once gall bladder was not visualized.